Slob dpon Padmas mdzad paʼi Khyuṅ bstod bźugs so - Padma Sambhava, ca. 717-ca. 762 (s.n., 1969)
Devotional piece addressed to Garuda as a deity from the Padma-dbaṅ-chen Yaṅ-gsaṅ-khros-pa (a form of Hayagriva) cycle; from the liturgy of Byes College of Sera Monastery and affiliates.